Basic Technical Skill Levels of Early Age Football Games Luwu District - Ilyas, Muslim Bin; Awal, Asri (UNIVERSITAS NEGERI MAKASSAR, 2025)
Based on the results of the survey analysis of the level of basic technical skills in early childhood soccer games in Luwu Regency, from the test data, the percentage of shooting data has a percentage of 5 people who died. Falls into the Very Low criteria with a percentage of 25%. 10 people fall into the Low criteria with a percentage of 50%, and 30 people fall into the Medium criteria with a percentage of 15%. And 2 people who fall into the Good criteria with a percentage of 10%. The ability to dribble the ball has a percentage of 17 people who fall into the Very Low criteria with a percentage of 85%. 3 people fall into the Low criteria with a percentage of 15%. Passing ability has a percentage of 7 people who fall into the Low criteria with a percentage of 35%, 6 people fall into the Medium criteria with a percentage of 30%, and 7 people fall into the Good criteria with a percentage of 35%. His heading ability has a percentage, namely 1 person who falls into the Very Low criteria with a percentage of 5%. 9 people fall into the Low criteria with a percentage of 45%, and 30 people fall into the Medium criteria with a percentage of 15%. And 7 people who fall into the Good criteria with a percentage of 35%. overall sample 20.